Abdul Haris Nasution's Contributions to Indonesian Military and Politics: 1955-1959 - Malinau, Wahyudi; Yuliantri, Rhoma Dwi Aria (Universitas Negeri Padang, 2023)
This article is a historical study that discusses Abdul Haris Nasution from a political perspective. This research explores Abdul Haris Nasution's career journey and his contributions to the Indonesian military and politics from 1955 to 1959. This study uses historical methods with steps, namely heuristic, verification, interpretation, and historiography. The historical sources used are primary sources, including the Chiefs Staff of mandate in the Republic of Indonesia, Instructions of the Central Warlord, The Mimbar Indonesia, and Nasution's writing books. Secondary sources from the results of previous research, which became the basis of Nasution's thought on the military and politics, such as Abdul Haris Nasution's role in the